2022
DOI: 10.1029/2021jd036393
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Atmospheric PM10 Concentration in China Using an Interpretable Deep Learning Model and Top‐of‐the‐Atmosphere Reflectance Data From China’s New Generation Geostationary Meteorological Satellite, FY‐4A

Abstract: Atmospheric particulate matter with an aerodynamic diameter less than 10 μm (PM 10 ) has a great impact on global environmental (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 93 publications
(113 reference statements)
0
7
0
Order By: Relevance
“…The maximum frequencies of dust aerosols in BTH and GZ, reaching approximately 10%, were observed at 2 and 4 km, respectively. Many studies have shown that dust aerosols originating from Northwest China and Mongolia can be transported to BTH and GZ (Huang et al., 2008), and the long‐range transport dust is one of the important contributors to PM10 during haze periods in these regions (Chen, Song, Huang, et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum frequencies of dust aerosols in BTH and GZ, reaching approximately 10%, were observed at 2 and 4 km, respectively. Many studies have shown that dust aerosols originating from Northwest China and Mongolia can be transported to BTH and GZ (Huang et al., 2008), and the long‐range transport dust is one of the important contributors to PM10 during haze periods in these regions (Chen, Song, Huang, et al., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the large-scale transmission of aerosols from Mongolia and the Gobi Desert west of mainland China, the occurrence frequency of dust aerosols in Beijing is also high (Zhang et al, 2009). Previous studies have demonstrated that long-distance transport of aerosols can lead to significant variations in the aerosol optical properties and distribution (Chen et al, 2022;Han et al, 2022;McKendry et al, 2011;Ramanathan & Feng, 2009).…”
mentioning
confidence: 99%
“…Using MODIS images and the deep belief network, Imani predicted the PM-suspended particles map for small places (Imani, 2021). In another study, Chen et al estimated PM10 values using a deep learning model and superior atmospheric re ectance data from a new geostationary meteorological satellite (Chen et al, 2022). Also, Shen et al developed a deep model to predict PM 2.5 directly using high atmospheric re ectance satellites (Shen et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Soluble aerosols such as sulfate, nitrate, and sea salt, and coarse aerosols such as dust, which can act as CCN, have important contributions to cloud/fog formation and precipitation [ 26 , 27 , 28 , 29 ], and is a breakthrough in understanding the transformation of LVEs from a microscopic perspective. CCN activation is generally affected by aerosol size distribution [ 30 ], chemical composition [ 31 , 32 ], aging [ 33 ], and mixing state [ 34 ].…”
Section: Introductionmentioning
confidence: 99%